Problems related to acute respiratory infection among under-5 children in Sorong, West Papua: a community diagnosis approach - Edo Prabudi Thamrin; Risma Kristi Utami; Fabianto Santoso; Ayu Ashari Thamrin; Siti Syahral Ain; Trevino Aristarkus Pakasi (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2019)
Acute respiratory infections (ARIs) are the leading cause of morbidity and mortality in children under five years, with a periodic prevalence of 25.9% in West Papua (2013). This study aims to explain the factors associated with ARIs in under-5 children in Sorong District, West Papua. This cross-sectional study was conducted in two districts, where trained medical students interviewed 135 mothers/caregivers by using a structured questionnaire and interviewed cadres and health workers for qualitative observation. About 85.5% of respondents stated that their children had ARIs in the previous two weeks (n=135), much higher than the data from Sorong District Health Office, which only reached 24.63%. Dominant risk factors were large household size, smoking at home, and improper handwashing habits. Only half of the respondents went to a physician in a primary care facility. Nearly half of the respondents had difficulty in accessing the facility. The majority of caregivers used over-the-counter or traditional medicine. Around 70% of respondents in Makbon Subdistrict did nothing to prevent the transmission of ARIs among children. ARIs remains a massive problem in the Sorong district. We need to educate the mothers/caregivers about the rational use of medicine and the prevention of ARIs, and also advocate for better access to clean water, sanitation, and healthcare facilities.